(untitled) (Journal of the Management Sciences, 2023)
The research was conducted to assess the effect of firm’s choice of system of processing financial transaction (Manual or Computerized system) on financial performance. The study focused particularly on the computerized accounting system of transaction processing which proxy was identified as the deployment of accounting software while firm performance was proxy with accuracy, timeliness and reliability of accounting information. Primary data was obtained by means of questionnaire administered to 38 respondents from 11 small and medium size firms that are into the production of paints in Anambra state, Nigeria. The study deployed Z-test statistical analysis tool to determine if there exists any significant effect of accounting software on firm performance. Finding showed that adoption of accounting software as a choice of accounting system has significant effect on financial performance of small and medium-size firms that are into paint production in Nigeria. The study concluded that computerization as a choice of accounting system has significant effect on the financial performance of small and medium size firms in Nigeria and thereby recommended, among other things, that other small and medium size firms that are yet to computerize their accounting system should do so in order to achieve (1) accuracy in data processing (2) timeliness of information processing and reporting (3) Reliability of result produced from the accounting system which ultimately translate to improvement in financial performance.